Selecting Monitoring Variables in the Manual Composting of Municipal Solid Waste Based on Principal Component Analysis (2018)
This paper proposes the use of principal component analysis performed on the correlation matrix for identifying the best variables for monitoring the composting of municipal solid wastes. Accordingly, 12 physicochemical and two microbiological parameters have been measured throughout the 7 weeks in which the compositing of 1300 kg of organic wastes obtained from MSW was carried out. All the analyses confirm a correct development of the composting process, and the final values fulfil the requirements of the Colombian legislation. The statistical analysis shows that four variables are sufficient for ensuring a suitable process development and, based on economic criteria and technical simplicity, the selected ones are as follows: respirometry, water retention capacity, ash content and moisture content. © 2018 Springer Science+Business Media B.V., part of Springer Nature